Inverse Columnar-Equiaxed Transition (CET) in 304 and 316L Stainless Steels Melt by Electron Beam for Additive Manufacturing (AM) - Miyata, Yuichiro; Okugawa, Masayuki; Koizumi, Yuichiro; Nakano, Takayoshi (Crystals (Basel), 2021)
According to Hunt’s columnar-to-equiaxed transition (CET) criterion, which is generally accepted, a high-temperature gradient (G) in the solidification front is preferable to a low G for forming columnar grains. Here, we report the opposite tendency found in the solidification microstructure of stainless steels partially melted by scanning electron beam for powder bed fusion (PBF)-type additive manufacturing. Equiaxed grains were observed more frequently in the region of high G rather than in the region of low G, contrary to the trend of the CET criterion. Computational thermal-fluid dynamics (CtFD) simulation has revealed that the fluid velocity is significantly higher in the case of smaller melt regions. The G on the solidification front of a small melt pool tends to be high, but at the same, the temperature gradient along the melt pool surface also tends to be high. The high melt surface temperature gradient can enhance Marangoni flow, which can apparently reverse the trend of equiaxed grain formation.